Evaluation of five shrubby legumes in comparison with Centrosema acutifolium, Carimagua, Colombia - Thomas, D.; Schultze-Kraft, Rainer (1990)
A small-plot grazing trial was conducted to assess selection by oesophageal-fistulated steers of 5 shrubby legumes adapted to acid, low-fertility soils (Centrosema arenarium, Desmodium strigillosum, D. velutinum, Flemingia macrophylla, and Tadehagi triquetrum) and the herbaceous Centrosema acutifolium, associated with native pasture. There was marked variation between seasons in legume consumption: In the first dry season the proportion of legume in the diet selected by fistulated steers was greater than the legume available in the pastures for all shrub species. In the second dry season, when there was significant off-season rainfall, legume consumption in 4 of the 5 shrub species was lower and appreciably less than the legume on offer. In the wet season legume selection was low, except for the herbaceous C. acutifolium. The N concentrations for legume leaf were high in the dry and wet seasons but digestibility (IVDMD) was low, especially in F. macrophylla. It was concluded that the shrubby species tested have a potential as dry-season forage when associated with native pastures but that in the light of apparently low IVDMD this potential needs to be assessed in terms of animal production.